The influence of oil prices on equity returns of Canadian energy firms - Sourav Batabyal; Robert Killins (Journal of Risk and Financial Management, 2021)
Using monthly data from January 2000 to August 2018, this paper examines how the Canadian oil and gas industry and individual firms' equity prices react to oil price fluctuations, which are measured by the traditional West Texas Intermediate (WTI) benchmark and the Canada-specific Western Canadian Select (WCS) benchmark. The findings provide support for the view that oil price movements are an important factor in explaining the equity returns of the overall industry and for many individual oil and gas firms in Canada. Both WTI and WCS measures provide statistically significant evidence, but the results support that WTI may still be the more relevant measure for Canadian-based firms. We also find that the spread between WTI and WCS has a minimal impact on the firms' equity returns. Additional tests for asymmetric impacts of oil price movements on Canadian oil and gas equity returns have provided little evidence, whereas time-varying impacts are found for a handful of firms. The empirical findings predicated on the holistic view of the impacts of oil price fluctuations on equity market returns will enhance investor confidence and strengthen the Canadian economy.
Keywords: E44; G12; L71; Q40; 330; Canada; equity returns; oil